Distribution operation and development of GlaxoSmithKline Bangladesh Ltd: a report on distribution process of a renowned consumer healthcare company in Bangladesh of Dhanmondi territory - Chowdhury, Azhar Amin (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.